NEIGHBOURHOOD TRAJECTORIES IN THE INNER CITIES OF PRAGUE AND TALLINN: WHAT AFFECTS THE SPEED OF SOCIAL AND DEMOGRAPHIC CHANGE?. Issue 4 (December 2016) - Temelová, Jana; Novák, Jakub; Kährik, Anneli; Tammaru, Tiit
ABSTRACT: This paper explores neighbourhood trajectories in the inner cities in terms of social and demographic change in a comparative perspective, and analyses the role of in situ change and residential mobility in this change. The research is based on a quantitative census‐based study of Prague (the Czech Republic) and Tallinn (Estonia) at a detailed neighbourhood level. The study shows that in spite of many political and historical similarities, the differences in local regulatory mechanisms and local contexts have led to different urban outcomes. Institutional rigidity and long‐term resistance to adjusting physical structures to a new social system have restrained change in Prague. The inner city of Tallinn has experienced much more social restructuring, replacements and displacements. High home‐ownership rates, early rent de‐regulation and no major public involvement in housing all contribute to the market‐led urban change in Tallinn.